Representasi Kekuasaan Perempuan Dalam Film “Resident Evil: Retribution - Dzuhria Wahyu Pratiwi; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Film is one of mass medias to find out the ideology of authority formed in the gender realm through the representation of the roles of women and men. The formation of character in Hollywood action film features women as complements and sweeteners for male heroes more often. The Film “Resident Evil: Retribution” aimed to find out the point of view used in describing women's authority in a film that engage female as the main characters. This research used a critical paradigm applying standpoint theory. The subject of this study was the scene in the film Resident Evil: Retribution that showed women's authority through observation. This study used the Semiotics data analysis method from Roland Barthes, idest Semiotic Analysis with a lexia and 5 reading codes including hermeneutic code, proarietic code, symbolic code, cultural code, and semic code. The results of Resident Evil: Retribution film research described women's power as represented through the main female character. Elements of authoriry in female characters showed the value of masculinity, with appearances such as male attributes, fighting, dominant, brave. The ideology appears in Resident Evil: Retribution was patriarchy, masculinity, women could be judged to have authority if they had masculine traits by appearing like men and managed themselves to look cool and scary.